Pengaruh Kompetensi Aparatur, Budaya Organisasi, dan Moralitas Individu terhadap Pencegahan Fraud dalam Pengelolaan Dana Desa: Studi Empiris pada Desa di Kecamatan Bangsal - Raharja, Dharma Putra; Sulistyowati, Erna (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study was to analyze whether apparatus competence, organizational culture, and individual morality influence fraud prevention in managing village funds. The benefits of this research are as a consideration in determining actions to prevent acts of fraud in the village government in Mojokerto Regency. This research uses quantitative methods using a descriptive research model. The data used in this research are primary data and secondary data, Primary data was collected using a questionnaire method while secondary data was obtained using literature reviews from various sources such as scientific articles, books and news articles. Sampling in this study used a purposive sampling technique with a total sample of 68 people. The tests carried out in this study were data quality tests, classical assumption tests, hypothesis testing, and multiple linear regression analysis. Data quality can be tested using validity and reliability tests. The classic assumption test used in this study consists of normality, multicollinearity, and heteroscedasticity tests, and hypothesis testing which consists of F tests, t tests, and the coefficient of determination. The results of the partial test in this study indicate that the competency of the apparatus and individual morality have a significant effect on fraud prevention, while organizational culture has no significant effect on fraud prevention.